2008
DOI: 10.1007/s11430-008-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

S-wave crustal and upper mantle’s velocity structure in the eastern Tibetan Plateau — Deep environment of lower crustal flow

Abstract: A teleseismic profile consisting of 26 stations was deployed along 30°N latitude in the eastern Tibetan Plateau. By use of the inversion of P-wave receiver function, the S-wave velocity structures at depth from surface to 80 km beneath the profile have been determined. The inversion results reveal that there is significant lateral variation of the crustal structure between the tectonic blocks on the profile. From Linzhi north of the eastern Himalayan Syntaxis, the crust is gradually thickened in NE direction; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 34 publications
5
26
0
2
Order By: Relevance
“…On both sides of the Longmenshan fault zone, the crustal thickness varies from 35 km in the east Sichuan Basin to 70 km in the west. A variety of geophysical factors demonstrated strong gradient changes on LFZ sides, such as electrical structure [4], gravity field [5], seismic wave attenuation [6], and P-wave velocity structure [7].…”
Section: Tectonic Backgroundmentioning
confidence: 99%
“…On both sides of the Longmenshan fault zone, the crustal thickness varies from 35 km in the east Sichuan Basin to 70 km in the west. A variety of geophysical factors demonstrated strong gradient changes on LFZ sides, such as electrical structure [4], gravity field [5], seismic wave attenuation [6], and P-wave velocity structure [7].…”
Section: Tectonic Backgroundmentioning
confidence: 99%
“…Geophysical studies have revealed its low-velocity and low-resistivity features within the mid-lower crust [10][11][12][13][14] and they are indicative of deep dynamics of the eastern Tibetan Plateau. The slow Pn-wave velocity indicates again that the Songpan-Ganzi mountain range has a weak lithospheric mantle with low rheologic strength, so that ductile deformation probably happens not only in the mid-lower crust but also in the uppermost mantle.…”
Section: Pn-wave Velocitymentioning
confidence: 99%
“…Actually, this boundary, reveled by the velocity and resistivity variation, extends throughout the crust and the upper mantle [10][11][12][13][14][15][16][17]. It plays a prominent role in dynamic process of controlling tectonic evolution of the Songpan-Ganzi mountain range and the Sichuan basin.…”
Section: Pn-wave Velocitymentioning
confidence: 99%
See 2 more Smart Citations